FILANTROPI KRISTEN: RESPONS TUBUH KRISTUS DALAM MENGATASI KEMISKINAN PADA MASA PANDEMI COVID-19 BERDASARKAN KISAH PARA RASUL 2:44-45 - Gde Ngurah Reza Rizaldy; Kayla Nathania Thayeb; Davin G. Sitompul (Vox Dei: Jurnal Teologi dan Pastoral, 2021)
Poverty is not a new problem in the context of life in Indonesia. Ironically, the current progress has not succeeded in overcoming this economic issue. This can be seen from the increasing poverty rate, and even worse by the presence of the COVID-19 pandemic. To address this economic issue, the life of the early Christian congregation showed its success in overcoming poverty, as evidenced in Acts 2:44-45. Thus, this article aims to formulate a concept called Christian Philanthropy, as a solution in addressing the economic difficulties experienced by the community, especially in the Church environment. So contextually, this research is useful for opening the perspective of individuals and the Church in seeing, as well as overcoming it by applying the concept of Christian Philanthropy which is viewed from the perspective of the New Testament. This research uses qualitative methods through hermeneutic studies. The results of the study found that the concept of philanthropy encourages the Church to respond to economic problems experienced by carrying out services comprehensively or evenly, both inwardly and outwardly, especially to marginalized groups.